Phase change materials confined into sunlight capturer sponge towards thermal energy harvesting and storage. (15th September 2021) - Fan, Dongli; Lu, Yaqing; Cao, Yufeng; Liu, Jie; Lin, Shaohui; Xiong, Dangsheng; Pan, Qinmin
Highlights: A sunlight capturer sponge (PBG) was designed for immobilization of organic PCMs. The PBG was derived from waste polybutadiene using sugar cube as the self-sacrificial template. The PBG effectively improved solar-thermal conversion capability of phase change composites (PCCs). PCCs exhibit excellent leak-proof capability and operational durability. Abstract: Polybutadiene (PB) waste recycling helps to reduce the ever-growing fossil energy demands because it is usually made from petroleum and natural gas. However, designing and developing a facile and low-cost way to achieve the efficient recycling of PB waste is still a formidable challenge because considerable energy is required to break the polymer chains. Herein, a 3D continuous porous sunlight capturer sponge derived from PB and octadecylamine-functionalized reduced graphene oxide (ODA-rGO) via self-sacrificial template strategy is proposed as supporting skeletons and high-efficiency solar-thermal conversion platform to construct a series of novel phase change composites (PCCs). The prepared PCCs are characterized by excellent leak-proof capability and thermal stability with a heat storage capacity as high as 171.5 J/g. More importantly, highly stable and reversible solar-thermal energy conversion and heat storage capacity without heat loss to the surrounding environment for the PCCs are also demonstrated. Hence the developed PCCs have a potential application in solar energy utilization systems and provide an excellent opportunity for the efficient recycling of PB waste.